Merger and Industrial Acceleration: Study at Indonesian Islamic Banking Industry - Kindy Miftah; Hendro Wibowo (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
The purpose of this research tries to feed the alternatives of merger between Islamic banks which becomes a form of recommendation to optimize the merger result, so it will contribute to the development of Indonesia’s banking sector in particular. Methodology of this study is using comparison technique utilize result of calculation valuation based on valuation theory in general with method discounted cash flaw (DCF). Valuation data processing using data past performance sharia banks is to plan future financial performance. Results of valuation will be conducted both with individual banks that will be merged and alternative merger determined. These findings implied from various possibility alternative mergers between sharia banks, there are 5 alternatives that are feasible considering the internal aspect such as tendency shareholder and condition sharia bank to be merged related to internal interest and external aspect namely scale of assets from merger banks and probability success from merger process.DOI: 10.15408/sjie.v6i1.4728